Please release - Powell, Nate 1978- (Top Shelf Productions, 2006)
Please Release collects four autobiographical stories, each linked by a series of open questions on work, mental disorders, aging, punk rock, developmental disabilities, horror movies, and a little unrequited love to boot. Recognized for his publications Tiny Giants and It Disappears, as well as his signature dream-like, luscious, and meticulous illustrations (reminiscent of Craig Thompson and Farel Dalrymple), this is Nate Powell's most direct and concrete work to date -- guaranteed to engage your brain and dazzle your senses